1986
DOI: 10.1017/s0022172400066171
|View full text |Cite
|
Sign up to set email alerts
|

Detection of diphtheria toxin antibodies in human sera in New Zealand by ELISA

Abstract: SUMMARYAn enzyme-linked immunosorbent assay (ELISA) was developed to detect IgG antibodies to diphtheria toxin in human serum. Serum samples obtained from 557 normal persons aged 1-65 years from different areas in New Zealand showed maximum antibody levels in the 1-9 years age group (95 1 %) and the least in the 60-65 years age group (38-1 %). The indirect ELISA is suitable for seroepidemiological survey study as it is simple to perform, economical and precise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This is particularly so when the Schick test, which is used today to distinguish the 'immune' from the 'non-immune', cannot be correlated with antibody response [17]. Although the distribution of antibody levels to DT in various populations is well documented [8, [18][19][20], there is little information on the antibody responses to individual fragments and defined epitopes. Apart from observations on a synthetic oligopeptide of the loop of fragment B (amino acids 188-201) which has been used successfully as a vaccine against lethal DT intoxication in guinea-pigs [15,16], very little is known about SPs derived from fragment A. This paper describes a survey carried out on several pools of adult human sera for antibodies to DT, and fragments A and B.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly so when the Schick test, which is used today to distinguish the 'immune' from the 'non-immune', cannot be correlated with antibody response [17]. Although the distribution of antibody levels to DT in various populations is well documented [8, [18][19][20], there is little information on the antibody responses to individual fragments and defined epitopes. Apart from observations on a synthetic oligopeptide of the loop of fragment B (amino acids 188-201) which has been used successfully as a vaccine against lethal DT intoxication in guinea-pigs [15,16], very little is known about SPs derived from fragment A. This paper describes a survey carried out on several pools of adult human sera for antibodies to DT, and fragments A and B.…”
Section: Introductionmentioning
confidence: 99%
“…However, as they are time consuming, cumbersome, expensive, and require large numbers of laboratory animals, they are being replaced by different serological methods (25, 31). ELISA is such an alternative and practical method and has been widely used for measuring diphtheria antibody levels in human and animal sera due to its simplicity, ease of automation, and objective interpretation (32–34). It has been reported that ELISA correlates well with in vivo and in vitro toxin neutralization tests and immune status of humans (29, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Its introduction has played a major role in reducing the incidence of tetanus an(l diphtheria to insignificance (Lau, 1986(Lau, , 1987a even though major outbreaks of pertussis have been reported in this country (Campbell Begg, 1984;Canterbury Hospital Board, 1987).…”
Section: Introductionmentioning
confidence: 99%